2004
DOI: 10.1562/2004-03-09-ra-106.1
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Behavior of a New Long-chain UV Absorber† Derived from 4-tert-Butyl-4′-Methoxydibenzoylmethane¶

Abstract: A new UV filter, the 1-(4-tert-butylphenyl)-2-decanyl-3-(4'-methoxyphenyl)-propane-1,3-dione, called C10-DBM, was prepared by grafting a 10-carbon aliphatic chain to the alpha-carbonyl position of 4-tert-butyl-4'-methoxydibenzoylmethane (BM-DBM), a well-known and often used UV filter. The UV-A absorption efficiency of organic solutions containing the new filter was tested and compared with identical solutions containing BM-DBM with or without irradiation (xenon lamp). The originality of this new filter is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…8 They reported that the photochemical -cleavage reaction of C10-BM-DBM possessing γ-hydrogen atoms produces the enol form of BM-DBM and 1-decene by the Norrish-II mechanism. As is known, this reaction is efficient if the T 1 state has an nπ* character.…”
Section: Resultsmentioning
confidence: 99%
“…8 They reported that the photochemical -cleavage reaction of C10-BM-DBM possessing γ-hydrogen atoms produces the enol form of BM-DBM and 1-decene by the Norrish-II mechanism. As is known, this reaction is efficient if the T 1 state has an nπ* character.…”
Section: Resultsmentioning
confidence: 99%
“…Because of antitumor and anti-inflammatory effects, dibenzoylmethane and its derivatives have attracted attention considering their potential use as a chemopreventive agents [2]. Furthermore, powerful sunscreen activity of DBM derivatives allows to use these compounds in the cosmetic industry as sunscreen agents [3,4]. The keto-enol tautomerization of b-diketones has attracted great interest and has been investigated extensively.…”
mentioning
confidence: 99%
“…IR and UV–vis spectra of poly (VDBM) are shown in Figures S4 and S5 (in Supporting Information), respectively. In the UV–vis spectrum, a strong absorption with maximum at around 350 nm was observed to confirm the presence of the enol form of 1,3‐diketone moiety 25. The temperatures for 5 and 10% weight loss ( T d5 and T d10 ) of poly(VDBM) were estimated by thermal gravimetric analysis (TGA) to be 328 and 356 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%